Vascular endothelial growth factor (VEGF)/VEGF-C mosaic molecules reveal specificity determinants and feature novel receptor binding patterns - Jeltsch, Michael; Karpanen, Terhi; Strandin, Tomas; Aho, Kukka; Lankinen, Hilkka; Alitalo, Kari (J Biol Chem, 2006)
Vascular endothelial growth factors (VEGFs) and their receptors play key roles in angiogenesis and lymphangiogenesis. VEGF activates VEGF receptor-1 (VEGFR-1) and VEGFR-2, whereas VEGF-C activates VEGFR-2 and VEGFR-3. We have created a library of VEGF/VEGF-C mosaic molecules that contains factors with novel receptor binding profiles, notably proteins binding to all three VEGF receptors ("super-VEGFs"). The analyzed super-VEGFs show both angiogenic and lymphangiogenic effects in vivo, although weaker than the parental molecules. The composition of the VEGFR-3 binding molecules and scanning mutagenesis revealed determinants of receptor binding and specificity. VEGFR-2 and VEGFR-3 showed striking differences in their requirements for VEGF-C binding; extracellular domain 2 of VEGFR-2 was sufficient, whereas in VEGFR-3, both domains 1 and 2 were necessary.